Single Deepest Vertical Pocket or Amniotic Fluid Index as Evaluation Test for Predicting Adverse Pregnancy Outcome (SAFE trial): A Multicenter, Open-Label, Randomized Controlled Trial - Kehl, Sven (Zeitschrift für Geburtshilfe und Neonatologie, 2018)
Objective of this randomized-controlled multicenter-trial was to determine whether the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique for estimating amniotic fluid volume is superior for predicting adverse perinatal outcome. Pregnant women at term were randomized in AFI or SDP group for assessing amniotic fluid at four unversitary hospitals. These two groups were not different with regards to primary outcome parameter (rate of postpartum admission to NICU), but concerning secondary outcome parameters: there were significantly more cases with the diagnosis oligohydramnios (9,8 vs. 2.2%), more induction of labour for oligohydrmanios (12.7 vs. 3.6%) and more abnormal CTG (32.3 vs. 26.2%) in the AFI group. None of the methods were superior to predict adverse perinatal outcome. However, the probability to diagnose oligohydramnios and to induce labour for oligohydramnios was higher when AFI technique was used.
EVALuna2:210072